MENINGKATKAN KESAN POSITIF PEMBACA TEKS PAKET PERJALANAN WISATA MELALUI KONJUNGSI - I Gusti Ngurah Adi Rajistha; Made Detrichyeni Winaya (Universitas Warmadewa, 2020)
Giving a positive impression in the text made is a basic thing to do in order to make readers feel comfortable reading texts given. However, not all writers can make texts that can express a positive impression. Application of grammatical cohesion, especially conjunction, is one of some ways that can be applied to reduce bounce rate to other websites. The aim of this research is to give a general overview of using conjunction in tour package texts by conveying semantic relation provided by all kinds of conjunctions. The data of this research were 41 tour package texts taken in the form of *.txt from a website named ganggabali.com. The data of this research were analyzed by applying the grammatical cohesion theory proposed by Halliday and Hasan (1976). The result of the analysis was presented by using formal and informal methods. This research shows all kinds of conjunction were applied to convey semantic relations among sentences in tour package texts. The use of the conjunctions, excluding other factors, can give readers a positive impression because by using conjunctions, the website owner can convey the semantic relation based on the kinds of conjunction applied.